Activating the Teaching-Research Nexus in Smaller Universities: Case Studies Highlighting Diversity of Practice - Boyd, William; O'Reilly, Meg; Bucher, Danny; Fisher, Kath; Morton, Anja; Harrison, Peter; Nuske, Elaine; Coyle, Rebecca; Rendall, Karyn (Journal of University Teaching and Learning Practice, 2010)
The teaching-research nexus (TRN) has become an important process in the modern University, providing both identity to university scholarship and a device for the integration of academics’ work. Over the last decade many reports have identified the need to both establish institution-wide processes to embed and support TRN, and assist in academic professional development in adopting TRN. This case study reports one such institutional project, focussing on one element of the staff development program, a TRN panel discussion by academics who have engaged TRN. The discussion was structured around the five TRN dimensions of: Learning through research; Research-led teaching; Researching teaching; Teaching informed research; Learning how to do research. By reflecting on their personal experiences, the presenters provided example and discussion of the diversity of options within TRN. In evaluating this event, we consider the diversity of subtlety of TRN. There are clearly advantages for students and staff alike, and TRN allows the curriculum to have a significant authenticity. In terms of teaching, research becomes a core learning tool and foundation of the curriculum. TRN then becomes the catalyst for merging boundaries between teachers and learners, lecturers and researchers: TRN becomes a truly two-way relationship.